New Spanish Late Cretaceous eusuchian reveals the synchronic and sympatric presence of two allodaposuchids. (October 2016) - Narváez, I.; Brochu, C.A.; Escaso, F.; Pérez-García, A.; Ortega, F.
Abstract: The recently described clade Allodaposuchidae includes European eusuchian crocodyliforms restricted to the Late Cretaceous (Campanian and Maastrichtian). A new allodaposuchid crocodyliform is here described based on two specimens from the upper Campanian–lower Maastrichtian fossil site of Lo Hueco (Cuenca, Spain). This new taxon, Agaresuchus fontisensis gen. et sp. nov., is described by two complete skulls and a lower jaw associated with one of them. This new species can be distinguished unambiguously from Lohuecosuchus megadontos, the other allodaposuchid known from the same fossil site. The presence of two allodaposuchid crocodyliforms in Lo Hueco allows the recognition of the synchronic and sympatric existence of two representatives of this clade for the first time. The new genus Agaresuchus, comprises a previously described Iberian allodaposuchid species, " Allodaposuchus " subjuniperus, as Agaresuchus subjuniperus, new combination. Highlights: A new Late Cretaceous European basal eusuchian crocodyliform is described. Iberian species Allodaposuchus subjuniperus is reassigned to new genus Agaresuchus. Phylogenetic analysis suggests Allodaposuchidae as the sister group of Crocodylia. Synchronic and sympatric presence of two allodaposuchids in a fossil site is revealed.